C.O.N.F.L.I.C.T. : an insider's guide to storytelling in factual/reality TV and film - Thirkell, Robert (Professional media practice., 2010)
""The recipe book of great television from one of the best TV makers in the world"" Jamie Oliver Story structure is a huge weakness for many factual or reality filmmakers and TV producers, who often concentrate on subject areas and issues rather than dramatic and memorable narrative. Consequently programmes fail to attract the audience or win any awards. In this book Robert Thirkell, the international consultant known as ''The TV Troubleshooter'' and renowned television producer, sets out a professional toolkit for developing a compelling storyline in factual and reality programmes and fi.